Effects of febuxostat on heart failure patients with asymptomatic hyperuricaemia: a retrospective cohort study - Wei Yuan; Zhaojun Wang; Xinguang Long (BMJ Open, 2025)
Objectives To investigate the effects of uric-acid-lowering therapy with febuxostat in asymptomatic hyperuricaemic patients with heart failure.Methods In this retrospective cohort analysis, we included consecutive hospitalised patients with heart failure and concomitant asymptomatic hyperuricaemia in Yangzhong People’s Hospital from 1 April 2018 through 1 April 2022. Febuxostat was used to lower serum uric acid. The primary endpoint was defined as a composite of cardiovascular death, recurrent hospitalisation and emergency room visit for cardiovascular (CV) reasons. Additional endpoints included changes in echocardiography measures, Kansas City Cardiomyopathy Questionnaire (KCCQ) scores and 6-minute walk test (6MWT) distance from baseline to the most recent clinic visit. Cox analysis was used to determine HR between febuxostat and the control group after adjustment for age, sex, body mass index, serum creatinine, atrial fibrillation and coronary heart disease and the Kaplan-Meier curve was used to describe survival.Results 979 patients were included in the final analysis (505 in the febuxostat group vs 474 in the control group). In a follow-up duration of 16±9 months, uric acid was significantly lower in the febuxostat group compared with the control group (p<0.001). There was no difference in the incidence of primary outcome between groups (HR 0.907 (95% CI 0.726 to 0.985), p=0.52). Changes in left ventricular ejection fraction, KCCQ scores and 6MWT distance from baseline to the latest record did not differ between groups. Subgroup analysis demonstrated no effect modification between treatment and age, sex, body mass index, atrial fibrillation and coronary heart disease. In multivariable Cox regression analysis based on cut-off value 5.35 of serum uric acid/serum creatinine ratio (SUA/sCr), SUA/sCr≥5.35 was an independent risk factor for primary outcome (HR 2.89 (95% CI 1.76 to 4.74), p<0.001).Conclusion Uric acid lowering therapy with febuxostat fails to produce clinical benefits in heart failure patients with asymptomatic hyperuricaemia.